PEMBERDAYAAN MASYARAKAT BERBASIS GREEN ECONOMY PENGOLAHAN SAMPAH MENJADI POC BAGI DESA SIMPANGAN CIKARANG UTARA - Tatik Juwariyah; Mitha Puspitasari; Sri Sulasmingsih; Mayanda M Santoni; Agus Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
North Cikarang Simpangan Village community is an urban community that inhabits densely populated areas. In RT 02/RW014, an average of 200-400 kilograms of organic waste is produced every day. Of course, this is very worrying if the waste is not managed and utilized in a new product. This article describes education to Simpangan Village residents regarding how to process household organic waste into liquid organic fertilizer (POC). Education is carried out in two stages, first starting with counseling regarding the importance of managing waste by sorting the types of waste into three types of waste, namely plastic waste or cans, paper waste, and organic waste. Based on data collection, 85% of the participants succeeded in practicing waste sorting. The second stage is training on how to produce POC without using an EM4 bio activator but utilizing local microorganisms. In this training, there were six groups of residents who practiced POC production methods with an average POC harvesting time of 13 days. The POC raw materials used are varied or come from various organic wastes such as vegetables, rice washing water, fruit skins, tempeh mushrooms, shrimp paste, shrimp heads, and brown sugar. The POC products were then tested for the content of four nutrients, namely C-organic, nitrogen, phosphorus, and potassium. Overall, the results of the nutrient content test are still far from the POC standard that is worth selling. However, from the results of the application of POC to plants, there was a significant effect in fertilizing plants. Based on the results of the monitoring and evaluation questionnaire related to the implementation of this educational activity, an average score of almost 100% of the residents was satisfied. Globally, the results of this activity can help solve environmental problems by educating the public on the importance of a sustainable ecosystem ABSTRAK: Masyarakat Desa Simpangan Cikarang Utara merupakan masyarakat urban yang mendiami wilayah padat penduduk. Di RT 02/RW 014 rata-rata dihasilkan sampah organik sekitar 200 – 400 kilogram setiap harinya. Tentu hal ini sangat memprihatinkan jika limbah tersebut tidak dikelola dan dimanfaatkan menjadi suatu produk baru. Artikel ini menjelaskan edukasi kepada warga Desa Simpangan terkait cara pengolahan limbah organik rumah tangga menjadi pupuk organik cair (POC). Edukasi dilakukan melalui dua tahap, pertama dimulai dengan penyuluhan terkait pentingnya mengelola sampah dengan memilah jenis sampah menjadi tiga jenis sampah yaitu sampah plastik atau kaleng, sampah kertas dan sampah organik. Berdasarkan pengambilan data diperoleh 85% peserta berhasil mempraktekkan pemilahan sampah. Tahap kedua adalah pelatihan cara memproduksi POC tanpa menggunakan bioaktivator EM4 tetapi memanfaatkan mikroorganisme lokal. Pada pelatihan ini terdapat enam kelompok warga yang mempraktikkan cara produksi POC dengan hasil rata-rata waktu pemanenan POC selama 13 hari. Bahan baku POC yang digunakan beraneka ragam atau berasal dari berbagai sampah organik seperti sayuran, air cucian beras, kulit buah-buahan, jamur tempe, terasi, kepala udang, dan gula merah. Produk POC selanjutnya diuji kandungan empat unsur hara yaitu C-organik, nitrogen, fosfor, dan kalium. Secara keseluruhan hasil uji kandungan unsur hara masih jauh dari standar POC yang layak jual. Namun demikian, dari hasil pengaplikasian POC ke tanaman terdapat pengaruh signifikan dalam menyuburkan tanaman. Berdasarkan hasil kuesioner monitoring dan evaluasi terkait pelaksanaan kegiatan edukasi ini diperoleh nilai rata-rata hampir 100 % warga puas. Secara global hasil kegiatan ini dapat membantu menyelesaikan masalah lingkungan dengan cara memberikan edukasi kepada masyarakat akan pentingnya ekosistem berkelanjutan (sustainable ecosystem).